A Massive Black Hole 0.8 kpc from the Host Nucleus Revealed by the Offset Tidal Disruption Event AT2024tvd - Yuhan Yao; Ryan Chornock; Charlotte Ward; Erica Hammerstein; Itai Sfaradi; Raffaella Margutti; Luke Zoltan Kelley; Wenbin Lu; Chang Liu; Jacob Wise; Jesper Sollerman; Kate D. Alexander; et al. (The Astrophysical Journal Letters)
Tidal disruption events (TDEs) that are spatially offset from the nuclei of their host galaxies offer a new probe of massive black hole (MBH) wanderers, binaries, triples, and recoiling MBHs. Here we present AT2024tvd, the first off-nuclear TDE identified through optical sky surveys. High-resolution imaging with the Hubble Space Telescope shows that AT2024tvd is 0 $\mathop{.}\limits^{\unicode{x02033}}$ 914 ± 0 $\mathop{.}\limits^{\unicode{x02033}}$ 010 offset from the apparent center of its host galaxy, corresponding to a projected distance of 0.808 ± 0.009 kpc at z = 0.045. Chandra and Very Large Array observations support the same conclusion for the TDE’s X-ray and radio emission. AT2024tvd exhibits typical properties of nuclear TDEs, including a persistent hot UV/optical component that peaks at L _bb  ∼ 6 × 10 ^43 erg s ^−1 , broad hydrogen lines in its optical spectra, and delayed brightening of luminous ( L _X,peak  ∼ 3 × 10 ^43 erg s ^−1 ), highly variable soft X-ray emission. The MBH mass of AT2024tvd is 10 ^6±1 M _⊙ , at least 10 times lower than its host galaxy’s central black hole mass (≳10 ^8 M _⊙ ). The MBH in AT2024tvd has two possible origins: a wandering MBH from the lower-mass galaxy in a minor merger during the dynamical friction phase or a recoiling MBH ejected by triple interactions. Combining AT2024tvd with two previously known off-nuclear TDEs discovered in X-rays (3XMM J2150 and EP240222a), which likely involve intermediate-mass black holes in satellite galaxies, we find that the parent galaxies of all three events are very massive (∼10 ^10.9 M _⊙ ). This result aligns with expectations from cosmological simulations that the number of offset MBHs scales linearly with the host halo mass.